Geology Of The American Girl-Padre Y Madre Gold Deposits Imperial County, California - J. O. Guthrie (Society for Mining, Metallurgy & Exploration, 1987)
Newmont has delineated a 600,000+ ounce gold reserve in the Cargo Muchacho Mountains. This is a desert range underlain by Proterozoic(?) Tumco Formation (gneiss) intruded by Jurassic granitic plutons, and cut by low angle shears of the late Cretaceous Chocolate Mountain Thrust event. Gold, associated with pyrite, quartz veinlets, and propylitic alteration, is emplaced along low angle shears. The mineralizing system, enriched in tungsten, copper, zinc and arsenic, was active during Eocene time. Gold reserves are found in eleven areas as moderate to high tenor deposits that may be mined by open pit and underground techniques. Eastmaque Gold Mines Ltd. is developing the deposit.